Ventricular bigemini in a patient with serologically positive dengue hemorrhagic fever - N. R., Salini; S., Srikantan (International Journal of Research in Medical Sciences, 2024)
Dengue epidemic is a major health problem in India. In expanded dengue syndrome major organs involvement and atypical manifestations have been increasingly reported. Cardiac involvement in dengue ranges from benign arrhythmias to fatal fulminant myocarditis. ECG changes usually secondary to myocarditis. Most common ECG abnormality Is bradycardia. Other ECG findings are ST segment depressions and elevation T wave abnormalities, sinus pauses ventricular ectopics, ventricular trigeminy, atrial fibrillation, heart blocks such as first-degree block and Mobitz type I second-degree AV block and bundle branch blocks. Most of the cardiac abnormalities are transient, but sometimes it can aggravate pre-existing conditions and even be fatal. So, assessing cardiac involvement in dengue patients is important for appropriate management. We are reporting a 55-year-old patient with dengue haemorrhagic fever presenting with ventricular bigeminy symptoms and markers indicative of cardiac compromise which improved after 1 week.